Effects of perioperative glycemic indicators on outcomes of endovascular treatment for vertebrobasilar artery occlusion - Gu, Mengmeng; Fan, Jin; Xu, Pengfei; Xiao, Lulu; Wang, Jinjing; Li, Min; Liu, Chaolai; Luo, Genpei; Cai, Qiankun; Liu, Dezhi; Ye, Lichao; Zhou, Junshan; et al. (Frontiers in Endocrinology, 2022)
Objective: Endovascular treatment (EVT) is, to date, the most promising treatment of vertebrobasilar artery occlusion (VBAO). The study was aimed to determine the influence of perioperative glucose levels on clinical outcomes in patients with acute VBAO treated with EVT. Methods: We retrospectively collected consecutive VBAO patients received EVT in 21 stroke centers in China. The associations between perioperative glycemic indicators (including fasting blood glucose[FBG], admission hyperglycemia, stress hyperglycemia ratio [SHR] and short-term glycemic variability [GV]) and various clinical outcomes were analyzed in all patients and subgroups stratified by diabetes mellitus (DM). Results: A total of 569 patients were enrolled. Admission hyperglycemia significantly correlated with increased risk of symptomatic intracranial hemorrhage (sICH) (odds ratio [OR] 3.24, 95% confidence interval [CI]: 1.40-7.46), poor functional outcomes at 90 days (OR 1.91, 95%CI: 1.15-3.18) and 1 year (OR 1.96, 95%CI: 1.20-3.22). Similar significant correlations exist between FBG, SHR, GV and all the adverse outcomes except higher levels GV was not associated with increased risk of sICH (OR 1.04, 95% CI: 0.97-1.12). Subgroup analyses showed that admission hyperglycemia, FBG and SHR were significantly associated with adverse outcomes in non-diabetic patients, but not in DM patients. While, GV was associated with poor functional outcomes regardless of diabetes history. Conclusions: Admission hyperglycemia, FBG, SHR and short-term GV in VBAO patients treated with EVT were associated with adverse outcomes. The results suggested that comprehensive evaluation and appropriate management of perioperative glucose might be important for patients with VBAO and treatment with EVT. Trial registration number: URL: http://www.chictr.org.cn/; Unique identifier: ChiCTR2000033211.